MOBILE APPLICATION FOR PRACTISING MATRICES AND GRAPHS - VOSTINAR, Patrik; PATRAS, Erik (Journal of Technology and Information Education, 2020)
The popularity of smartphones and expansion of their usage into various areas in the last years caused that users want to have to control everything on their phone. The paper deals with the description of the educational mobile application for practicing operations with matrices and graphs. The created mobile app is free, available in the Google Play Store. The main functionality of the application is the possibility of practicing unlimited operations with matrices and graphs. The main aim of creating this application is to create an educational tool that can improve the motivation to study the subject Discrete Mathematics for Computer Science.
Keywords: mobile applications; Android; matrices; graphs